Phase-controlled converter for Nd:YAG laser flashlamp driver - Hadi Yaacob Mohd Ikhwan, Bidin Noriah, Mat Daud Yaacob, (N/A, 2009)
Phase-controlled converter for Nd:YAG laser flashlamp driver by Hadi Yaacob Mohd Ikhwan, Bidin Noriah, Mat Daud Yaacob,